Phytochemical profile, antioxidant, cytotoxic and anti-inflammatory activities of stem bark extract and fractions of Ailanthus excelsa Roxb.: In vitro, in vivo and in silico approaches - Priyanka R. Sapkal; Anilkumar U. Tatiya; Sandip D. Firke; Vivek K. Redasani; Shailendra S. Gurav; Muniappan Ayyanar; Prasad G. Jamkhande; Sanjay J. Surana; Rakesh E. Mutha; Mohan G. Kalaskar (Heliyon, 2023)
This study aimed to assess the phytochemical composition, in vitro antioxidant, cytotoxicity, and in vivo anti-inflammatory activities of the methanolic extract of Ailanthus excelsa (Simaroubaceae) stem bark and its fractions. Quantitative phytochemical analysis revealed that methanolic extract and all fractions contained a high level of flavonoids (20.40–22.91 mg/g QE), phenolics (1.72–7.41 mg/g GAE), saponins (33.28–51.87 mg/g DE), and alkaloids (0.21–0.33 mg/g AE). The antioxidant potential was evaluated in vitro using a range of assays, i.e., DPPH•, ABTS radical scavenging ability, and total antioxidant capacity. The chloroform and ethyl acetate fractions showed stronger antioxidant activity than the methanol extract. In vitro cytotoxic activity was investigated in three human tumor cell lines (A-549, MCF7 and HepG2) using the SRB assay. In addition, the in vivo anti-inflammatory effect was assessed by carrageenan-induced paw edema in rats. The chloroform fraction showed a more pronounced effect by effectively controlling the growth with the lowest GI50 and TGI concentrations. The human lung cancer cell line (A-549) was found to be more sensitive to the chloroform fraction. Furthermore, the chloroform fraction exhibited significant anti-inflammatory activity at a dose of 200 mg/kg in the latter phase of inflammation. Besides, methanol extract and ethyl acetate fraction revealed a significant cytotoxic and anti-inflammatory effects. The chloroform fraction of stem bark showed a strong anti-inflammatory effect in experimental animals and significant COX-2 inhibitory potential in the in vitro experiments. GC-MS analysis of chloroform fraction identified the phytochemicals like caftaric acid, 3,4-dihydroxy phenylacetic acid, arachidonic acid, cinnamic acid, 3-hydroxyphenylvaleric acid, caffeic acid, hexadeconoic acid, and oleanolic acid. The in-silico results suggest that identified compounds have better affinity towards the selected targets, viz. the BAX protein (PDB ID: 1F16), p53-binding protein Mdm-2 (PDB ID: 1YCR), and topoisomerase II (PDB ID: 1QZR). Amongst all, caftaric acid exhibited the best binding affinity for all three targets. Thus, it can be concluded that caftaric acid in combination with other phenolic compounds, might be responsible for the studied activity. Additional in vivo and in vitro studies are required to establish their exact molecular mechanisms and consider them as lead molecules in developing of valuable drugs for treating oxidative stress-induced disorders, cancers, and inflammations.